The Significance Relationship between Palynomorph Fossil Preservation and Grain Size in Rock: Case Study of Walat and Batuasih Formations, Sukabumi, West Java - Rizki Satria Rachman; Winantris Winantris (JURNAL GEOCELEBES, 2023)
Palynomorph is dust-sized material that is resistant to acids and can be preserved as fossils in sedimentary rocks. Fossil content in rocks is very diverse which is influenced by various factors, one of this factors is the texture of rock in form of grain size. The Walat and Batuasih Formations are sedimentary rock formations that have variety of grain sizes. This research aims to examine relationship or correlation between grain size and palynomorph preservation in rocks with case studies in the Walat and Batuasih Formations. 42 samples were taken from measured stratigraphic section and analyzed both grain size and palynomorph content. Statistical analysis with Normality Test using Shapiro Wilk and Liliefors; Homogeneity Test using Levene Test; and Non-Parametric Associative Test using Spearman Rank was conducted to see the relationship of these variables. Result, the Walat and Batuasih Formations have conglomerate, sandstone, mudstone and coal lithologies with quite variety of palynomorphs. Statistical results show that all variables have data that are not normally distributed with tendency to be non-homogeneous. Moreover, it was found that the grain size of rock had significant effect on the preservation of palynomorphs in the rock. Clay grains has positive correlation of 0.613 and sand grains has negative correlation of -0.653. This shows that the finer the grain size, the more effective the preservation of palynomorphs is.